(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to determine the level of both functional creativity and organizational commitment among academics at King Abdulaziz University from the perspective of department heads and supervisors. It also sought to identify whether there were statistically significant differences in levels of functional creativity and organizational commitment based on gender, years of experience, and academic rank. Additionally, the study aimed to explore the nature of the correlation between functional creativity and organizational commitment among department heads and supervisors at King Abdulaziz University. To achieve the study’s objectives, a descriptive correlational method was employed. The study population consisted of all department heads and supervisors at King Abdulaziz University, totaling (272) individuals. A simple random sample of (247) was selected. An electronic questionnaire was developed, comprising two main sections: the first measured functional creativity, and the second measured organizational commitment. The validity and reliability of the instrument were confirmed, and it was then administered to the sample. The results showed that the overall mean score for functional creativity among department heads and supervisors at King Abdulaziz University was (3.98), indicating a high level of response. Similarly, the overall mean score for organizational commitment was (4.16), also indicating a high level of response. The findings revealed no statistically significant differences in functional creativity based on gender, years of experience, or academic rank. Likewise, no statistically significant differences were found in organizational commitment based on gender or academic rank. However, there were statistically significant differences in organizational commitment based on years of experience, favoring those with one year or more. Moreover, the results indicated a strong positive correlation between functional creativity and organizational commitment among department heads and supervisors at King Abdulaziz University. Based on these findings, the researcher recommends training department heads and supervisors in motivational leadership methods by organizing annual programs in empowering and transformational leadership, in cooperation with the Deanship of Academic Development. Furthermore, the study recommends linking functional creativity to incentive and recognition systems by modifying performance evaluation forms to include creativity as a key indicator and offering rewards for innovations and practical suggestions.